OC-020 Broad cross-genotypic antibody responses to hcv e1e2 in clinical cohorts: epitope targets and clinical associations. (22nd June 2015) - Swann, R; Robinson, M; Cowton, V; Mills, PR; Barclay, S; McLauchlan, J; Patel, A
Abstract : Introduction: HCV remains a major cause of liver morbidity and mortality worldwide. The capacity of HCV to rapidly mutate poses a challenge for immunisation as a preventative strategy. Increasing evidence suggests that the breadth of anti-HCV antibody response plays an important role in clinical outcomes. 1 Understanding virus and host factors associated with production of antibodies able to neutralise multiple strains of virus will help inform future vaccine design. We aimed to i) investigate the presence of broadly neutralising patient antibody (bNAb) responses targeting E1 and E2, ii) characterise the epitopes targeted by these bNAbs and iii) determine any association with clinical and host factors in patients chronically infected with HCV (CHCV). Method: Purified serum IgGs were obtained from 52 CHCV patients without evidence of other liver pathologies. These were tested by ELISA for binding to E1E2 proteins derived from different HCV genotypes (gt), and for neutralising activity to these glycoproteins in the pseudoparticle (HCVpp) system. In a subset of 21 gt 1 infected patients, we assessed neutralising responses to a panel of HCVpp incorporating 11 gt 1 envelope glycoproteins and competition of bNAbs with conformational antibodies to known epitopes on E2. Results: IgGs from 10 (19%) patients were able to neutralise HCVpp from >4/6 subgenotypes tested (bNAb group). Heat-map analysis of competition with antibodies to known domains showed that IgGs from the bNAb group competed with multiple epitopes of E2 (rather than a single region). HCV viral load was significantly lower in those with broad ELISA binding (p = 0.036). The bNAb group had significantly lower median liver fibrosis (Fibroscan®) readings than those neutralising <3 subgenotypes (p = 0.046). In the subgroup of 21 patients tested for neutralising ability against a gt 1 panel, individuals clustered into 9 broad, 7 moderate and 5 weak neutralisers on heat-map analysis. Broad neutralising profile was associated with lower levels of liver cirrhosis (p = 0.007). Broad intragenotypic neutralisation status was also associated with AA/AG at SNP rs9275224 in the HLA-DQB1 gene but there was no association with IL28B genotype. Conclusion: We have shown that patients with bNAb responses to HCV usually target multiple functional epitopes on the E1E2 protein. Host genotype may play a role in the ability to raise such responses and requires further exploration. Broadly neutralising antibodies are associated with lower rates of fibrosis in chronic infection and further work to determine if they are protective is warranted. Disclosure of interest: None Declared. Reference: Osburn WO, Snider AE, Wells BL, et al . Clearance of hepatitis C infection is associated with the early appearance of broad neutralizing antibody responses. Hepatology 2014;59(6):2140–51